Height, weight, body fat, static strength and explosive power of girls aged 10-14 tested with "Eurofit" test - Maciaszek, Janusz (Kinesiologia Slovenica, 2001)
The aim of the study is a multifaceted analysis of the relationships between height, weight and body fat with static strength and explosive power, determined in accordance with the Eurofit test. The subject sample consisted of 1,574 girls 10 - 14 years of age. Body height, weight, the thickness of five skinfolds, static strength and explosive power were measured. The logarithm of the sum of five skinfolds was computed and accepted as a measure of fatness. The subjects were divided into three groups on the basis of this measure: lean, average and fat. Pearson correlation, partial correlation, linear, non-linear regression, analysis of variances and student's t-test were used for statistical analysis. Body fat is the only parameter, which significantly affects both static strength and explosive power in every age. Body fat determined explosive power (r = -0.33 to r = -0.45) more than static strength (r = 0.17 to r = 0.30). The relations are linear in some age groups and non-linear in others. Curvilinear relationships between body fat and both static strength (14-year-olds) and explosive power (11- and 14-year-olds) were observed. In this instance, the explosive power is determined by body fat to a greater extent (D = 21.3% and 17.4%) than static strength (D = 6.0%), as indicated by higher values of the coefficient of determination. Analysis of variance showeda high level of significance (p<0.01) of the differences in all age groups. This means that body fat is a factor, which differentiates between levels of static strength and explosive power. The above observations confirm earlier results indicating the need for using multifaceted methods of data analysis to study the relations between somatic parameters and physical fitness.
Keywords: dekleta; Eurofit; morfološke lastnosti; raziskave; telesna pripravljenost